Gender Differences in Students' Mathematics Self-Concept and Academic Burnout - Farshid Paidar; Ahmad Amirhooshangi; Reza Taghavi (Shiraz University of Medical Sciences, 2017)
Background: Mathematics self-concept and academic burnout are one of the most important psychosocial factors in academic achievement. Objectives: The current study aimed to compare gender differences in mathematics self-concept and academic burnout in the students. Methods: The sample included 140 male and 90 female first-grade high school students selected via one-stage cluster sampling method. The current descriptive study applied mathematics self-concept scale by Radi in 2011 and also school burnout inventory by Salmela-Aro, Naatanen in 2004. Data were analyzed using independent t-test. Results: The results showed that the mean of scores in mathematics self-concept and its subscales components (skills and capabilities, mathematics enjoyment and mathematics avoidance) were not significantly different between male and female students (P > 0.05), while the mean scores of academic burnout and its components (exhaustion, cynicism, inadequacy) were higher in male students (P < 0.05). Conclusions: Mathematics self-concept and its components were the same between male and female students, but academic burnout and its components were higher in males than females.